Proceedings of SPE Annual Technical Conference and Exhibition 2006
DOI: 10.2523/102590-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid Fracturing or Proppant Fracturing in Carbonate Formation? A Rock Mechanics View

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAcid fracturing is performed to improve well productivity in acid-soluble formations such as limestone, dolomite, and chalk. Hydrochloric acid is generally used to create an etched fracture, which is the main mechanism for maintaining the fracture open during the life of a well. Proppant fracturing is an alternative option that has been applied in carbonate formations. In certain areas, proppant fracturing has been used as a standard stimulation method for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The compressive failure of asperities is postponed. This finding is in line with Abass et al (2006) observations. The well that might be represented by the pair CP-13 and CP-14, CP-19 and CP-20 could be good candidate to acid fracturing once the conductivity curves passes within or near acid fracturing envelope.…”
Section: Conductivity Results -supporting
confidence: 95%
“…The compressive failure of asperities is postponed. This finding is in line with Abass et al (2006) observations. The well that might be represented by the pair CP-13 and CP-14, CP-19 and CP-20 could be good candidate to acid fracturing once the conductivity curves passes within or near acid fracturing envelope.…”
Section: Conductivity Results -supporting
confidence: 95%
“…To study the effect of acid on rock strength, we have systematically measured two parameters in each experiment in addition to the conductivity, the RES before and after acidizing, and the change in the vertical depth on the acidized surface by means of a 3D surface profile apparatus 5 . From these measurements we determined the coordinates of the high and low points of the etched core to compare with the coordinates of the RES measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Even though formation hardness tests were not performed on the core samples, from their results, authors observed that more etched volume did not always result in higher conductivities. Abass et al 5 have performed experimental studies to investigate the effect of creeping on acid fracture conductivity. They recognized that acid weakens the contact points, causing a susceptible surface to creeping.…”
Section: Introductionmentioning
confidence: 99%
“…Abass et al (2003) has demonstrated that in case of high in-situ stress, an etched fracture may significantly lose conductivity as a result of creeping effect.…”
Section: Acid Fracturingmentioning
confidence: 99%